Pengaruh Keamanan dan Kepercayaan Terhadap Minat Pengguna QRIS di Toko Deni Store Ajamu, Labuhanbatu - Yunira Rambe; Midrawati Hasibuan; Sri Ayla (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of security and trust on the interest in using QRIS as a digital payment method at Deni Store in Ajamu, Labuhanbatu. The research adopts a quantitative approach, utilizing primary data collected through surveys. Data analysis is conducted using descriptive tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Data processing is carried out using SPSS version 22.0 to ensure the accuracy of the research findings. The results indicate that security significantly influences the interest in using QRIS. This is evidenced by the t-count value of 4.753, which is greater than the t-table value of 1.295, with a significance level of 0.000, which is below 0.05. Additionally, trust also has a significant impact on the interest in using QRIS, with a t-count value of 6.392, exceeding the t-table value of 1.295, and a significance level of 0.000, which is less than 0.05. Simultaneously, security and trust contribute 92.8% to the interest in using QRIS at Deni Store Ajamu, Labuhanbatu. These findings highlight that security and trust are key factors in driving QRIS adoption among users. Therefore, SMEs and digital payment service providers must enhance transaction security and build consumer trust to expand QRIS adoption in the business sector.